A Smart Hybrid Energy System Grid for Energy Efficiency in Remote Areas for the Army - Umberto Berardi (Energies, 2020)
The current energy inefficiencies in relocatable temporary camps of the Armed Force troops create logistic challenges associated with fuel supply. The energy needs of these camps are primarily satisfied by diesel engine generators, which imply that a significant amount of fuel needs to be continuously provided to these camps, often built in remote areas. This paper presents an alternative solution, named Smart Hybrid Energy System (SHES), aiming towards significantly reducing the amount of fuel needed and minimizing transportation logistics while meeting camp energy demands. The SHES combines the existing diesel generators with solar power generation, energy storage, and waste heat recovery technologies, all connected to a microgrid, ensuring uninterrupted electricity and hot water supplies. All components are controlled by an energy management system that prioritizes output and switches between different power generators, ensuring operation at optimum efficiencies. The SHES components have been selected to be easily transportable in standard shipping 20 ft containers. The modularity of the solution, scalable from the base camp for 150 people, is designed according to available on-site renewable sources, allowing for energy optimization of different camp sizes in different climates.